Sport officiating recruitment, development, and retention - Livingston, Lori; Forbes, Susan L.; Wattie, Nick; Cunningham, Ian (Routledge, Taylor & Francis Group, 2020)
"Sport officials are tasked with maintaining order and adjudicating sport contests. Given their multifaceted role in enforcing rules, standardizing competitions, and keeping sport safe for all participants, they are a requisite part of the sport workforce. With ongoing reports of annual attrition rates in officiating in excess of 20-35% for various sports around the world, there is more than ample evidence that officiating dropout is a persistent, pervasive, and global challenge underpinned by multiple contributing factors including, but not limited to, the threat of verbal and physical abuse. Moreover, despite worldwide recognition and growing interest in the problem, there has not been a comprehensive resource for sport scientists and practitioners studying or working to reverse the ongoing trend. Sport Officiating; Recruitment, Development, and Retention provides a 'state of the science' summary in the emerging area of inquiry limited to sport officiating recruitment, development, and retention; and, provides insight and evidence-based approaches to the development of successful long-term officiating development (LTOD) programs. This book is a primary reference work using a multifaceted, holistic, and evidence-based approach to integrate key findings from the sport science literature to date in suggesting and providing real-world solutions to the practical issues faced by sport organizers. Sport Officiating; Recruitment, Development, and Retention is a key resource for researchers interested in the development of sport officials and for sport practitioners aiming to implement LTOD programs at any level within sport systems"--
Includes bibliographical references and index
Routledge is an imprint of the Taylor & Francis Group, an informa business
Keywords: Sports officials / Recruitment; Sports officials / Training of; Sports officiating; SPORTS & RECREATION / Coaching / General; SPORTS & RECREATION / Sports Psychology; SPORTS & RECREATION / History